KEPUASAN WISATAWAN DI OBYEK WISATA BATURRADEN DAN WANA WISATA BATURRADEN, KABUPATEN BANYUMAS - , RAHADYAN PRAMUDHITO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Baturraden Tourism Object and Baturraden Tourism Forest is located in Baturraden Tourism Regions, Banyumas Regency, Central Java Province. Both of these tourist destinations have different levels visiting frequency. Analysis of tourist satisfaction is a parameter to indicate the difference in terms of the level of visit tourist destinations. This study aims to determine the differences of the level of tourist satisfaction Baturraden Tourism Object and Baturraden Tourism Forest, and the relationship between the tourists' profile with tourists' satisfaction in both tourism destinations. The method used in this study is the Customer Satisfaction Index (CSI). It is used to determine the level of tourist satisfaction. Furthermore, the results of tourist satisfaction index are analyzed by using Mann-Whitney U-test statistical analysis to determine the differences in terms of the level of satisfaction in the Baturraden Tourism Object and Baturraden Tourism Forest. Chi Kuadrat statistical analysis is also used to determine the relationship between tourists' profile and tourists' satisfaction in Baturraden Tourism Object and Baturraden Tourism Forest. Tourists who visited Baturraden Tourism Object have a satisfaction index score of 0.76, and these are included in the category of 'satisfied', while tourists who visited to Baturraden Tourism Forest have a satisfaction index score of 0.65, and these are included in the 'fairly satisfied' category. The results of the statistical test Mann-Whitney U test showed a significant difference in the level of satisfaction between Baturraden Tourism Object and Baturraden Tourism Forest, because the value of sig-2-tailed 0.000 < rather than the value of criticism 0.05. Meanwhile, Chi square analysis shows that the tourists' job which belongs to Tourist profile, have a significant relationship with the satisfaction in the Baturraden Tourism Object. On the other hand, Baturraden Tourism Forest has no significant relationship between tourists' profile and satisfaction.